Behaviors of Large-Rupture-Strain Fiber-Reinforced Polymer Strengthened Reinforced Concrete Beams Under Static and Impact Loads - Ye, Zenghui; Zhao, Debo; Sui, Lili; Huang, Zhenyu; Zhou, Xiaoqing (Frontiers in Materials, 2020)
Reinforced concrete (RC) structures may be damaged seriously when subjected to impact loading, and it is necessary to strengthen existing structures to improve their impact resistance. Large-rupture-strain fiber-reinforced polymer (LRS-FRP) is a promising material to strengthen RC structures under impact because of its good deformation capacity. This article shows experimental studies on performance of LRS-FRP strengthened RC beams under static and impact loads. The effects of FRP types, loading rate, and the usage or nonusage of end-anchorages on the strengthening efficiency were investigated. The experiment demonstrates LRS-FRP laminate with end-anchorage (EA) to be an appropriate strengthening technique for RC beams under both static and impact loading. The beams strengthened with end-anchored LRS-FRP presented greater ductility than their carbon fiber-reinforced polymer counterpart under static loading, and the end-anchored LRS-FRP strengthening system reduced the maximum deflection and damage of strengthened beam under impact significantly. However, the end-anchorage was more susceptible to damage and failure when the loading rate increased from static to impact. Therefore, the end-anchorage and the end-anchorage-FRP connection should be designed with caution for impact condition.